The effect of the appearance fake of function on perceived benefits and product attitude - Seong, Eunhye; Kim, Gwi-gon (International Journal of Innovative Research and Scientific Studies, 2025)
This study empirically investigates how the type of fake product, particularly the Appearance Fake of Function, influences consumers’ product attitudes and the underlying psychological mechanisms. Fake fashion products were initially classified into three types based on prior studies, with this research focusing on the Appearance Fake of Function. A survey of 796 adults (739 valid responses) was conducted online and offline, and data were analyzed using SPSS 22. Results showed that the Appearance Fake of Function negatively affected perceived functional benefits but positively influenced symbolic benefits. Perceived functional benefits reduced product attitude, whereas symbolic benefits enhanced it. The relationship between the fake type and product attitude was partially mediated by perceived benefits and moderated by product type (utilitarian vs. hedonic). The study suggests that while symbolic benefits improve attitudes, functional benefits may lower them due to cognitive dissonance. Therefore, marketing strategies should emphasize symbolic value, especially tailored to product type. Future research should empirically examine other fake types and explore more nuanced product categorizations.